Patient Satisfaction with Clinical Laboratory Services in Public Health Sector Hospitals of Azad Kashmir, Pakistan - Khalid, Bilal; Ayyub, Fareeha; Nasim, Midhet; Babar, Ayesha; Khan, Saad Alam (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To determine patient satisfaction and factors affecting patient satisfaction with laboratory services in Azad Jammu & Kashmir (AJK). Study Design: Cross-sectional study. Place and Duration of Study: Seven District Headquarter Hospitals, DHQ Neelum, DHQ Hattian Bala, DHQ Pallandari, DHQ Bagh, DHQ Kotli, DHQ Bhimber and DHQ Mirpur, Kashmir Pakistan from Dec 2019 to Feb 2020. Methodology: The patients who were referred from the Outdoor Patient Department of the hospital for undergoing investigative tests were included, and patients of age less than 18 and critically ill patients were excluded. Results: The total number of respondents included in the study was 400, with the median score of patient satisfaction with laboratory services being 59 (19), ranging from 32 to 100. Statistically significant disparities in client satisfaction were observed in different DHQ hospitals (p-value=0.01) with Mirpur (63) and Pallandri (40) showing the extreme variation. Residential area, age, and education level were also identified as statistically significant determinants of patient satisfaction (p-value <0.05). Conclusion: patient satisfaction with laboratory services in public hospitals of AJK was very low, and targeted strategies are needed to improve the overall quality of these services.